PENGARUH DOMPET DIGITAL TERHADAP KEMUDAHAN TRANSAKSI (STUDI KASUS PENGUNJUNG DI BANDUNG INDAH PLAZA) - Aliah, Siti; Terawati, Mira Teram; Christian , Ivan (Publika Citra Media, 2024)
Digital wallet acceptance has a fairly good development in Indonesia. This is shown by the value of digital wallet transactions in Indonesia in February 2021 is known to have a total of 19.2 trillion or grew by 26.4 percent from year to year. This study aims to determine the magnitude of the influence of digital wallets on the ease of visitor transactions at Bandung Indah Plaza (BIP). This study uses a type of survey research that uses tests and questionnaires as data collection instruments. By using quantitative approaches and qualitative approaches, and testing hypotheses using statistical test tools. Data quality test consists of validity and reliability test, Instrument test. The statistical methods used are simple linear regression analysis, correlation coefficient analysis, hypothesis testing and determination coefficient analysis with the help of the SPSS program. Based on the results of data analysis, it shows that the influence of digital wallets on the ease of transactions.